PENGARUH KESESUAIAN TIPE KEPRIBADIAN PADA KINERJA MAHASISWA AKUNTANSI - Apriayani P, Putu (Buletin Studi Ekonomi, 2016)
Abstract :The influence of personality suitability of accounting student performance. This research aims to confirm if a right personality type will make a better performance. With as many as 193 people (purposive sampling was used to get this amount), this research finally found a link between personality type and accounting student. The student performance was determined by their GPA level, while personality type determined with MBTI. The data analysis technique in this research is a linear regression with dummy variable. Results shows that there is an effect of the existence of a right personality type with accounting student performance, according to Myers-Briggs Type Indicator (MBTI) Key words: personality type, Myers Briggs Type Indicator (MBTI) test, student performance
Keywords: personality type, Myers Briggs Type Indicator (MBTI) test, student performance